2016
DOI: 10.1038/srep22455
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of the invasive potential of Glioblastoma cells by mTOR inhibitors involves modulation of NFκB and PKC-α signaling

Abstract: Glioblastoma (GBM) is the most aggressive type of brain tumors in adults with survival period <1.5 years of patients. The role of mTOR pathway is documented in invasion and migration, the features associated with aggressive phenotype in human GBM. However, most of the preclinical and clinical studies with mTOR inhibitors are focused on antiproliferative and cytotoxic activity in GBM. In this study, we demonstrate that mTOR inhibitors-rapamycin (RAP), temisirolimus (TEM), torin-1 (TOR) and PP242 suppress invasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 61 publications
4
48
1
Order By: Relevance
“…Maintaining SOX2 activation by PI3K/AKT pathway activity provided a first molecular link between the 3q26 gene products PIK3CA and SOX2. Of note, mTOR, a downstream target of PI3K/AKT signaling, was previously identified as a regulator of glioma cell invasion and proposed as target for controlling cell invasion (6). However, we found that PI3K/AKT directly regulates SOX2 activity in ways that do not (evidently) involve mTORC1.…”
Section: Interplay Between 3q26 Genescontrasting
confidence: 51%
“…Maintaining SOX2 activation by PI3K/AKT pathway activity provided a first molecular link between the 3q26 gene products PIK3CA and SOX2. Of note, mTOR, a downstream target of PI3K/AKT signaling, was previously identified as a regulator of glioma cell invasion and proposed as target for controlling cell invasion (6). However, we found that PI3K/AKT directly regulates SOX2 activity in ways that do not (evidently) involve mTORC1.…”
Section: Interplay Between 3q26 Genescontrasting
confidence: 51%
“…In fact, when considering all the properties of stem-like GBM-initiating cells such as cell proliferation, expression of stemness antigens as well as loss of cell aggregation and increased cell migration, all of them are affected by mTOR inhibition [5, 6, 9, 16, 23, 24]. …”
Section: Discussionmentioning
confidence: 99%
“…46 We have previously demonstrated that mTOR inhibitors, RAP, TEM, TOR, and PP242, reduced PKC activity in GBM cells. 26 In this context, we show here that TEM and TOR markedly reduced the Figure 7. mTOR inhibitors reverse the neurosphere formation promoted by PMA and OSM.…”
Section: Discussionmentioning
confidence: 51%
“…We recently reported that mTOR inhibitors-rapamycin (RAP), TEM, TOR, and PP242-suppressed invasion and migration induced by tumor necrosis factor-alpha (TNFα) and tumor promoter (phorbol-myristate-acetate (PMA)) in human GBM cells. 26 Given that invasion and migration are characteristics associated with mesenchymal phenotype and stemness-like features in GBM, the aim of this study was to investigate the potential of mTOR inhibitors in affecting the mesenchymal markers and stemness. We demonstrate that TEM and TOR inhibit mesenchymal markers and stem cell-like traits induced by PMA and oncostatin-M (OSM).…”
Section: Introductionmentioning
confidence: 99%